Innovation versus acquisition: panel evidence on the market value of intangible capital in Europe - Glova, Jozef (Serbian Journal of Management, 2026)
This study examines the influence of intangible investments on firm valuation in terms of the comparative influence of internally generated research and development and externally purchased intangible fixed assets. Using panel data for 247 listed European firms over the span of a decade, this paper uses fixed effects and Generalized Method of Moments estimators to adjust for unobserved heterogeneity and endogeneity problems. The findings reveal a strong and stable positive and statistically significant association between research and development intensity and Tobin’s Q, stressing the focus of the market on endogenously driven innovation as the strongest driver of firm value. In comparison, the effect of acquired intangibles is less strong and statistically less intense, revealing that capital markets focus more on endogenous innovation efforts than on intangible acquisition. Results of the study contribute to the literature on intangible capital by offering empirical findings on the impact of investment styles on firm value, with significant implications for policy making, innovation management, and corporate finance.